Confirming the presence of HTLV-1 infection and the absence of HTLV-2 in blood donors from Arequipa, Peru Confirmação da presença de infecção por HTLV-1 e ausência de infecção por HTLV-2 em doadores de sangue de Arequipa, Peru - Nadia Carmela Santos Quispe; Edwin Bengoa Feria; Elizabeth de los Santos-Fortuna; Adele Caterino-de-Araujo (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
Epidemiological studies conducted in Peru disclosed HTLV-1 to be prevalent in different ethnic groups, and found HTLV-2 in some Amazonian Indians and in men who have sex with men. No data concerning HTLV-1/2 infection in blood donors from Arequipa, a highlands region in southern Peru, is available. We searched for the presence of HTLV-1 and HTLV-2 antibodies in 2,732 serum samples obtained from blood donors from this geographic area. HTLV-1/2-specific antibodies were detected using an enzyme-linked immunosorbent assay (ELISA) and were confirmed by Western blot (WB). Reactive sera had their blood bags discarded from donation, and the demographic characteristics of the donors were analyzed. Thirty-five sera (1.2%) were HTLV seroreactive by ELISA, and 25 were confirmed HTLV-1-positive by WB. One serum disclosed HTLV-positivity, and the remaining nine serum samples showed indeterminate results by WB; three of which had an HTLV-1 indeterminate Gag profile. The median age of HTLV-positive individuals was 34.6 years; 27 were male and eight were female. All individuals were from southern Peru: 27 from Arequipa, five from Puno, and three from Cuzco. HTLV co-positivity with hepatitis B (five sera) and syphilis (one serum) were detected. Previous transfusion and tattooing were observed in two and one individuals, respectively. No serum was positive for HTLV/HIV co-infection. This study confirmed, for the first time, HTLV-1 infection and the absence of HTLV-2 infection in blood donors from Arequipa, Peru and suggests vertical transmission as the major route of HTLV-1 transmission and acquisition in this geographic region. Estudos epidemiológicos conduzidos no Peru apontam a infecção por HTLV-1 como prevalente em diferentes grupos étnicos e por HTLV-2 restrita a alguns índios da região Amazônica e a homens que fazem sexo com homens. Não existem dados sobre a infecção por HTLV-1/2 em doadores de sangue de Arequipa, região montanhosa do sul do Peru. Portanto, o presente estudo pesquisou anticorpos anti-HTLV-1 e HTLV-2 em 2.732 ...